Notice to submit financial proposal as a single source for the procurement of goods, works and services mentioned in the letter to BRAC University - BUCG (Brac University, 2023)
This record consists of general correspondence regarding notice to submit financial proposal as a single source for the procurement of goods, works and services mentioned in this letter to BRAC University.